Harmful Trademarks Towards a New Understanding of Moral Bars in GCC Registration - Farah, Nadiya (Munich Intellectual Property Law Center - MIPLC, 2019)
Between 2013-2017, around 115 EU trademark applications were rejected on morality and public order grounds. In the GCC (six Arab and Islamic countries), anecdotal evidence suggests some refusals have bemused foreign applicants and highlighted cultural blindspots. In this context, this work examines how three Arab Gulf states that have Islamic law as the main source of legislation and large expatriate communities, apply moral bars to trademark registration. It draws comparison with Western jurisdictions. Three main questions are explored: 1) To what extent do immoral or borderline trademarks/goods proceed to registration in conservative Islamic countries that apply trademark law in conformity with Shari'a law? 2) What reasoning is guiding decisions? 3) Can a concept of 'harm' improve our understanding of the power of trademarks and thus the moral thresholds that countries set?The author is an innovation and IP commercialisation professional. She acquired a passion for trademark law while completing a Master of Laws in 'Intellectual Property and Competition Law' in Munich, Germany. She is now pursuing a career in trademark law in the UK.